Tailoring the pore structure of carbon nanofibers for achieving ultrahigh-energy-density supercapacitors using ionic liquids as electrolytes - Kim, Chang Hyo; Wee, Jae-Hyung; Kim, Yoong Ahm; Yang, Kap Seung; Yang, Cheol-Min (ROYAL SOC CHEMISTRY, 2016)
The low energy density of commercially available activated carbon-based supercapacitors has limited their widespread applications. In the current work, we demonstrated fabrication of carbon nanofiber-based supercapacitors that exhibited ultra-high energy density by rationally tailoring their pore structure in an ionic liquid system. To gain control on the pore structure, three different methods were employed for the synthesis of an electrospinning-derived freestanding carbon nanofiber web. They are incorporation of a pore generator (i.e., tetraethyl orthosilicate) in the electrospinning step, physical activation (e.g., H2O or CO2), and hydrogen treatment. We observed finely tuned pore sizes ranging from 0.734 to 0.831 nm and accompanying changes in BET surface areas ranging from 1160 to 1624 m(2) g(-1). The entrapped TEOS within the electrospun organic nanofiber web provided high tuning ability of the pore structure in the following carbonization step, and decreased the activation energy of the pore formation. Both high specific capacitance (161 F g(-1)) and ultra-high energy density (246 W h kg(-1)) were achieved when the pore size on the surface of carbon nanofibers matched with the ionic size of the electrolyte. Our results demonstrate the importance of a finely tuned pore structure to secure high-temperature operable carbon nanofiber-based supercapacitors with ultrahigh energy density using ionic liquids as electrolytes.
Keywords: DOUBLE-LAYER CAPACITORS; ACTIVATED CARBONS; SURFACE-AREA; HYDROGEN TREATMENT; ELECTROCHEMICAL PROPERTIES; SIZE DISTRIBUTION; ATOMIC-HYDROGEN; 4 V; ELECTRODES; PERFORMANCE